Characterisation of high temperature coatings by miniature specimen testing and inverse approaches - Wen, Wu (2019)
Coatings, e.g. thermal barrier coatings (TBCs), have been widely used for many high temperature engineering applications to protect the components from such severe operating environments. An improved understanding of the mechanical behaviour of the coatings is required for assessing the reliability and performance of the critical components as well as developing novel TBCs. Inverse methods were developed based on nonlinear optimisations to acquire the mechanical properties from experimental results in conjunction with analytical solutions or finite element (FE) modelling. They were proved to be capable of determining the elastic-plastic and creep properties of materials from various experimental data with different material constitutive models. For example, it was demonstrated that the inverse method was able to converge to the optimised mechanical properties within 5% error compared to the predefined values, taking the load-displacement curves and the surface profile of the indented specimen for the multi-objective optimisation. Some issues encountered during the development process, such as the scaling of the optimised quantities and the loading paths applied for FE modelling, were also investigated. Theoretical studies were carried out for a two-material system (coating-substrate) regarding the individual and compound elastic-plastic/creep behaviour. The inverse method was adopted and demonstrated to be able to extract the material properties of an unknown material based on the known material behaviour and the experimentally determined compound material behaviour. Experiments were carried out for a P91 steel (used as the substrate material for a coated system) and a thermally sprayed CoNiCrAlY coating (typically used as the bond coating of TBCs) using existing miniature specimen testing methods, such as the small punch tensile (SPT) and creep (SPC) tests and micro/nano-indentation tests. The experiments were carried out for the temperature range from room temperature (RT) up to 700°C. The ductile-to-brittle transition temperature (DBTT) of the CoNiCrAlY was studied examining the variation of the mechanical properties, ductility and the failure patterns. The fracture surfaces of the tested SPT specimens of the CoNiCrAlY coating were studied using scanning electron microscopy (SEM). Brittle fracture was observed at temperatures from RT to 500°C while typical ductile fracture was observed at 700°C. Significant scattering was observed for the SPT tests at lower temperatures, indicating that the small punch test was less effective as a mechanical testing method for brittle materials due to early cracking and the complex multi-axial stress state during the deformation process. A novel two-material miniature specimen testing method was developed for the applicable scale of coatings (total thickness of 0.5mm, minimum coating thickness of 0.15mm for the coating-substrate specimen). Single-material miniature tensile and creep tests were carried out for a P91 steel and the same CoNiCrAlY coating used for the SPT tests. Good agreements were achieved between the SPT and miniature tensile tests regarding the DBTT of the CoNiCrAlY coating. It should be noted that excellent consistency and repeatability were observed for the miniature tensile testing results at all temperatures, suggesting that this miniature testing method had the potential to become a universally applicable technique considering that it was also easier to interpret because the stress state in the uniform section was close to that in the conventional uniaxial tensile testing specimen. The load-displacement data obtained from the miniature tensile tests were used to extract the elastic-plastic properties of the CoNiCrAlY coating using the inverse method. The characterised stress-strain behaviours were applied for the FE modelling of SPT tests and some representative behaviours were obtained compared to the corresponding experimental results, such as the early cracking at the lower temperatures and the location of the ductile fracture at higher temperatures. The results of this study provide miniature specimen characterisation methods with great potential for the applications for coatings. The numerical and experimental work has set a solid foundation for the future work of two-material and multi-material systems, e.g. characterisation of the elastic-plastic and creep behaviour of a coated system consists of a CoNiCrAlY coating and the substrate of a P91 steel or other coating-substrate systems.